The Impact of Organizational Culture and Motivation on Employee Performance Using Compensation as an Intervening Variable at PT. Inti Prima Rasa - Nani Puryati; Masydzulhak Djamil (Dinasti International Journal of Education Management And Social Science, 2023)
The goal of this study was to examine the relationship between organizational culture and motivation and employee performance at PT. Inti Prima Rasa using compensation as an intervening variable. a quantitative descriptive research design was used by the authors in 200 participants made up the sample of 133 respondents for survey. The Partial Least Squares approach is an analysis technique (PLS), Research results prove that (1) motivation influences compensation positively and significantly, (2) Compensation is positively impacted by organizational culture.(3) motivation influences performance positive and significant. (4) Organizational culture has a positively and significantly influence on performance. (5) Employee performance is positively and significantly affected by compensation. (6) Employee performance is significantly impacted and improved by motivation through compensation. (7) Organizational culture has a favorable and considerable impact on employee performance through compensation as an intervening factor. Motivation and organizational culture must be improved in order to improve the performance of employees of PT. Inti Prima Rasa in order to carry out its duties and obligations properly.